2020
DOI: 10.2337/db20-907-p
|View full text |Cite
|
Sign up to set email alerts
|

907-P: Impact of Using a Digital Therapeutic and Blood Glucose Meter on Glycemic Control and Variability

Abstract: Background: High out of pocket expenses have led to poor diabetes self-management and glycemic control in India. This study evaluates the impact of an iPDM (integrated personalized diabetes management) on blood glucose (BG) control. Methods: Study participants (n=286) used an iPDM consisting of the Accu-Chek® Active BG meter and the Wellthy Care™ digital therapeutic platform (WDTx), which allowed them to log BG values while receiving artificial intelligence-powered real-time feedback and self-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The performance of the WC DIP has been previously studied in the real-world setting in patients with chronic diseases such as type 2 diabetes (T2D) and hypertension ( 15 – 18 ). In patients with T2D, the use of a 16-week structured self-management program delivered with the WC mobile application showed improved glycemic control, weight reduction, and self-management ( 15 , 16 ). In patients with T2D and hypertension previously using WC for their diabetes management, the addition of hypertension self-management education and self-reported blood pressure (BP) measures showed that the platform facilitated glycemic control while achieving a significant reduction in BP ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the WC DIP has been previously studied in the real-world setting in patients with chronic diseases such as type 2 diabetes (T2D) and hypertension ( 15 – 18 ). In patients with T2D, the use of a 16-week structured self-management program delivered with the WC mobile application showed improved glycemic control, weight reduction, and self-management ( 15 , 16 ). In patients with T2D and hypertension previously using WC for their diabetes management, the addition of hypertension self-management education and self-reported blood pressure (BP) measures showed that the platform facilitated glycemic control while achieving a significant reduction in BP ( 17 ).…”
Section: Introductionmentioning
confidence: 99%